Whitened Résumés: Race and Self-Presentation in the Labor Market - Kang, Sonia K.; DeCelles, Katherine A.; Tilcsik, András; Jun, Sora (Administrative science quarterly, 2016)
Using interviews, a laboratory experiment, and a résumé audit study, we examine racial minorities' attempts to avoid anticipated discrimination in labor markets by concealing or downplaying racial cues in job applications, a practice known as "résumé whitening." Interviews with racial minority university students reveal that while some minority job seekers reject this practice, others view it as essential and use a variety of whitening techniques. Building on the qualitative findings, we conduct a lab study to examine how racial minority job seekers change their résumés in response to different job postings. Results show that when targeting an employer that presents itself as valuing diversity, minority job applicants engage in relatively little résumé whitening and thus submit more racially transparent résumés. Yet our audit study of how employers respond to whitened and unwhitened résumés shows that organizational diversity statements are not actually associated with reduced discrimination against unwhitened résumés. Taken together, these findings suggest a paradox: minorities may be particularly likely to experience disadvantage when they apply to ostensibly pro-diversity employers. These findings illuminate the role of racial concealment and transparency in modern labor markets and point to an important interplay between the self-presentation of employers and the self-presentation of job seekers in shaping economic inequality.